Control design and implementation of a spiral spring energy storage system connected to a grid via PMSG - Yang Yu; Zengqiang Mi; Xudong Guo; Xitong Niu; Xiaojiang Zheng; Chenjun Sun (CSEE Journal of Power and Energy Systems, 2018)
For an innovative spiral spring energy storage system, the permanent magnet synchronous generator (PMSG) is utilized as the energy conversion device due to its simple structure, low weight and high torque. During power generation, the output torque and moment of inertia of the spiral spring are changing continuously and simultaneously and the parameters of the PMSG show uncertainties. Furthermore, the DC link voltage of the converter should be stable and the power injected into the grid needs to be controlled. First, the change features of the external power source and the uncertainties of the generator's internal parameters are expressed as the comprehensive disturbances, which are introduced into the dynamic model of the PMSG and also modify the dynamic model. Then, the high gain observers are utilized to estimate the comprehensive disturbances, and an improved robust backstepping control scheme integrating L2 gain and high gain observers is proposed. Secondly, the gridside inverter controller for the DC voltage loop and reactive power loop is designed based on the backstepping theory. Finally, hardware implementation is fulfilled to verify the presented algorithm. The results show that high gain observers are able to accurately estimate the external and internal interferences; the proposed control scheme can effectively suppress the external and internal interferences and guarantees output current, operating speed of the PMSG and output reactive power to correctly track respective references, and effectively stabilize the DC link voltage.